The atlas complex - Blake, Olivie (Blake, Olivie. Atlas series., 2024)
Vulnerable to the lethal terms of their recruitment, six Alexandrians grapple with the ethics of their astronomical abilities while the outside world mobilizes to destroy them, forcing them to decide what they're willing to betray for limitless power and who will be destroyed along the way.